호박씨 가루로 제조한 마카롱의 품질 특성 - 홍수지(Su Ji Hong); 윤혜현(Hye Hyun Yoon) (동아시아식생활학회지, 2020)
This study investigated the quality characteristics of macarons prepared using pumpkin seed powder. Macaron samples were prepared by replacing almond with 0%, 25%, 50%, 75%, and 100% pumpkin seed powder. The moisture contents of the samples with increasing amount of pumpkin seed powder ranged from 7.65 to 11.06% for macaron batter and from 3.43 to 5.25% for macaron products. With increasing amount of punpkin seed powder, there was a decrease in the L-values and redness and an increase in the yellowness of macarons. Both the spread factor and baking loss rate of macarons increased with increasing amount of pumpkin seed powder. Texture profile analysis revealed a significant increase in the hardness, springiness and gumminess with increasing pumpkin seed powder. Acceptance tests by 79 consumers showed that the control had the significantly highest scores for color (p<0.001). However no significant differences were observed among the samples with respect to odor, taste, texture and overall acceptance. KCI Citation Count: 4